Pemahaman dan Perilaku Keluarga dalam Penanganan ISPA Pneumonia pada Anak Balita di Wilayah Puskesmas Kadungora Kabupaten Garut - Nita Kardilah (Yayasan Literasi Sains Indonesia, 2025)
Pneumonia remains one of the leading causes of death among children under five in Indonesia. In Garut Regency, a total of 9,865 pneumonia cases were recorded in 2023, with Kadungora Primary Health Center reporting 276 cases of acute respiratory infection (ARI) with pneumonia in children under five during the same period. Most cases experienced delays in treatment due to low family knowledge and awareness regarding early symptoms and initial actions to take. This study aims to describe family understanding, health-seeking behaviors, and factors influencing the management of ARI pneumonia in children under five. A qualitative method was employed through in-depth interviews with two families of children diagnosed with pneumonia and two local healthcare workers. The results revealed that most families failed to recognize the early signs and symptoms of pneumonia, tended to rely on traditional remedies, and had limited access to health information. However, families who had received health education from community health volunteers responded more promptly and appropriately in seeking medical care. Key factors influencing family behavior included socioeconomic conditions, knowledge level, and access to information. This study highlights the crucial role of active healthcare provider involvement and community-based education in increasing awareness and promoting timely management to reduce morbidity and mortality from pneumonia in children under five.